The Military Coup In Georgia And The Newspaper “Kuji” In Kutaisi - Khatchapuridze, Lola; Khatchapuridze, Luiza (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
In 2000 Kutaisi organization of Helsinki Union founded the newspaper “Kuji” which functioned for two years, published 39 editions, and was spread to whole Georgia. The diversity and relevancy of the newspaper was defined by the several rubrics: Information from the Kolki castle” published the statements of the persecuted supreme council, the agenda of sessions and meetings; “Fragments from our present”, “false mirror and reality”, “Scenes from the nearest past of Kutaisi” (describes the life of Kutaisi residents of coup time, breaking up the rallies); “Different news of Georgia”, “History lessons”, “Our faith”, “Poetry”, “Science”, “Spot”, “Kuji post” ( published gratitude letters sent from readers and opinions about different issues?. We can state that the Kutaisi newspaper “Kuji” is the chronicler of the period of Georgia. It is written by all the residents of Georgia about their defeated home country. It will help future generations to create the general picture of Georgia at the end of the 20th century.